Dynamics Of Investment Regulation: A Legal Review Of Law No. 25 Of 2007 On Investment In Indonesia In Overcoming The "Investment Ghost" - Ireina Rahayanti Nurmal (Jurnal Syntax Transformation, 2023)
Investment is one of the important factors in economic growth. Through investment, a country can obtain the capital and technology needed to develop its economy. Indonesia is one of the countries that has great potential to attract foreign investment. However, Indonesia also has a number of challenges in attracting investment, one of which is the "investment ghost". This study aims to provide an overview of how investment regulations in Indonesia have changed and evolved in an effort to overcome the "investment ghost". This study utilizes a qualitative research method. Data is collected through a literature study of various laws and regulations, scientific literature, and related documents. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results show that in overcoming investment ghosts, the government overcomes these problems with Law No. 25/2007 on Investment (UUPM). The UUPM adopts the principles of transparency, ease of doing business, and fair business competition. The UUPM also gives greater authority to local governments in organizing investment affairs, which is expected to speed up the investment licensing process and improve coordination between the central government and local governments. Therefore, the UUPM has succeeded in creating a more conducive and attractive investment climate for investors.